Answer:
for this case we have the following functions:
f (x) = x + 8
g (x) = -4x - 3
Subtracting the functions we have:
(f - g) (x) = f (x) - g (x)
(f - g) (x) = (x + 8) - (-4x - 3)
Rewriting:
(f - g) (x) = x + 8 + 4x + 3
(f - g) (x) = 5x + 11
Answer:
D. (f - g) (x) = 5x + 11
Step-by-step explanation:
30=-5(6n+6)
30=-5×6n-5×6
30=-30n-30
30+30=-30n
60=-30n
60/-30=-30n/30
-2=n
In the parallelogram ABCD, join BD.
Consider the triangle Δ ABD.
It is given that AB > AD.
Since, in a triangle, angle opposite to longer side is larger, we have,
∠ ADB > ∠ ABD. --- (1)
Also, AB || DC and BD is a transversal.
Therefore,
∠ ABD = ∠ BDC
Substitute in (1), we get,
∠ ADB > ∠ BDC.
The answer is 3 :) hope helps
The answer is 6m - 6 = 8m + 4
Hope this helps please give brainless!!!